2013
DOI: 10.5376/ijms.2013.03.0016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Total Nitrogen and Total Phosphorus in Major River Systems of Sundarbans Mangrove Forest, Bangladesh

Abstract: Mangrove provides a unique ecological environment for diverse communities and Sundarbans is a rapidly changing ecosystem due to various anthropogenic activities. In order to assess the spatial and temporal variation of total Nitrogen and total Phosphorus concentration in Major River Systems of Sundarbans, a study was carried out from September, 2010 to February, 2011. Fourteen sampling location from major River systems were chosen. During post monsoon and winter seasons the range of total Phosphorus (0.326~0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…They found that the distribution of nutrients is influenced by tidal cycle as indicated by changes in tidal height. Rahaman et al (2013b), who made field observations in the Sundarbans intertidal mangrove forest to analyze spatial and temporal variations in phytoplankton abundance and species diversity, reported that spatial and temporal variations in water quality conditions of the RSs indicate the influence of various climatic and local forcing functions.…”
Section: Tidal Variations Of Nutrientsmentioning
confidence: 99%
“…They found that the distribution of nutrients is influenced by tidal cycle as indicated by changes in tidal height. Rahaman et al (2013b), who made field observations in the Sundarbans intertidal mangrove forest to analyze spatial and temporal variations in phytoplankton abundance and species diversity, reported that spatial and temporal variations in water quality conditions of the RSs indicate the influence of various climatic and local forcing functions.…”
Section: Tidal Variations Of Nutrientsmentioning
confidence: 99%
“…Moreover, Sonneratia apetala was introduced into Yigluo Bay in 1993 and was highly adaptive, so it grew very fast in the low intertidal zone (Chen et al 2004;Wang et al 2013). Because of the varied environmental conditions consequent upon the change of soil elevation mentioned above, soil attributes in mangroves may vary among the different mangrove communities (Ferreira et al 2010;Rahaman et al 2013;Yu et al 2013) and this may have implications for SOC fractions in mangroves. In this context, it is noteworthy that few pedological studies have been carried out along a microtopographic gradient of a mangrove ecosystem and upon SOC fractions in mangrove ecosystems.…”
Section: Introductionmentioning
confidence: 96%
“…Phosphate concentration in the study area non-significantly varied among the sampling stations (p˃ 0.05) but significant variation was found among the sampling months (p˂ 0.05). Rahaman et al (2013a) also observed lower phosphate concentration ranging from 0.05 to 0.42 mg/L with an average of 0.12 mg/L in the Rupsha-Pasur river system. The average phosphate value of 0.323 mg/L was recorded in this study was higher than that of 0.115 mg/L, as has been reported by Wahid et al (2007).…”
Section: Nutrients Parametersmentioning
confidence: 76%
“…The Pearson correlation matrix (Table 2) showed that the concertation of ammonium in PRE had significantly positive correlation with surface water temperature (r = 0.45), salinity (r = 0.28) and TDS (r = 0.29) but showed negative correlation with DO concentration (r = 0.42) and pH (r = 0.42). Rahaman et al (2013a) recorded NH 3 -N concentrations between 0.02 and 0.38 mg/L with an average of 0.14 mg/L 0.00 with significantly higher concentrations ranging from 0.26 to 0.38 mg/L during the monsoon season and relatively lower amounts ranging from 0.02 to 0.08 mg/L during the post-monsoon and winter periods. Wahid et al (2007) reported an average ammonia concentration of 0.054 mg/L, whereas the earlier studies reported that ammonia concentration ranged from 0.001 to 0.33 mg/L with an average of 0.043 mg/L (IWM, 2003).…”
Section: Nutrients Parametersmentioning
confidence: 96%
See 1 more Smart Citation